THE ROLE OF MOTIVATION IN TEFL: A SUPPORTIVE FACTOR IN LANGUAGE LEARNING ACHIEVEMENT - Fitria Damayanti (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2015)
Abstract: Motivation is an important factor in success language learning. The effect of motivation influences a great deal toward the process of teaching and learning. A teaching is successful if the teacher is able to produce motivated students in doing so the students will be more interested in the lesson and it will facilitate them in understanding the lesson. Many experts and research has been done to find out the effect of motivation and how it facilitates both teachers and student in teaching learning process. The most significant research on motivation is conducted by Gardener and Lambert and then on continuous issues have emerged and looked upon. There are several types of motivation like intrinsic, extrinsic, integrative and instrumental.Keywords: motivation, success language learning, intrinsic, extrinsic, integrative and instrumental